CHINESE-RUSSIAN PARTNERSHIP AND STRATEGIC COOPERATION - Liu Fenghua (Сравнительная политика, 2019)
For most of the time since the establishment of the Chinese-Russian strategic partnership, diplomatic interaction was the main area of strategic cooperation between the two parties. Diplomatic interaction manifested generally in two aspects: maintaining a favorable environment and conditions of international security and a commitment to establish a new international political and economic order; supporting each other’s efforts to protect national sovereignty and territorial integrity. With start of “One Belt, One Union” project in 2015 and broadening of regional cooperation betweenChinaandRussia, the Chinese-Russian strategic partnership entered the stage of “common development”. Based on high-level diplomatic support,ChinaandRussiawill cooperate with each other in their respective economic and social development strategies and regional integration strategies in order to explore fully their potential for cooperation in order to achieve common development goals.